LITERASI PINJAMAN ONLINE YANG BIJAK DI DESA GUNUNGSARI KECAMATAN GUNUNG SARI KABUPATEN SERANG - Sutisna Sutisna; Nani Rohaeni (Jurnal Abdimas Bina Bangsa, 2024)
Online loans are increasing day by day, both in terms of the amount of credit disbursed and the number of borrowers. However, the presence of online loans also has a negative impact in the form of many people getting into online loan debt. This negative impact is likely due to the public's lack of understanding of online loans. Therefore, it is necessary to carry out outreach with the aim of providing understanding about online loans and increasing awareness of borrowing online. The socialization method was carried out by holding online loan literacy training for residents of Gunungsari village, Gunungsari District, Serang Regency. The socialization results showed that the public's understanding of online loans was in the sufficient category (71.7%). After socialization through training, there was an increase in knowledge about online loans by 16.7%.